Determination of biochemical indicators of the functional state of livers of white rats for one-time internal intra-abdominal administration of the mixture of nanoparticles of metals (Ag, Cu, Fe, MnО2) - Roman'ko, Marina (ScienceRise: Biological Science, 2017)
There was established the hepatotoxic effect of the mixture of colloid dispersions of nanoparticles of metals (mixture NPMe: Ag, Cu, Fe, MnО2) compared with the mixture of salts of correspondent metals at the one-time intra-abdominal administration to white rats that has the expressed dose-depending effect. Mechanisms of the hepatotoxic effect of NPMe mixture is doses 1,0, 2,0 and 4,0 mg/kg of a body mass are in formation of the oxidation stress in an animal organism that is accompanied by the increase of enzyme activity of indicative AsAt and HGT and catalase, inhibition of AlAT, AP and general AOA (р≤0,05). The intensification of urea formation along with the increase of the glucose level (р≤0,05) in plasma of rats that received NPMe in increased doses indicates the evident intensification of processes of elimination of nanoparticles that is in the direct proportion to the time of admission and energetic supply of animals. At the absence of prooxidant effect and regulation of indicators of AOS in rats’ organisms it was proved, that NPMe mixture in dose 0,3 mg/kg of a body mass is biocompatible and has the adaptogenic effect compared with salts of correspondent metals that colloid dispersions of nanoparticles of essential metals can be considered as a prospective substance of drugs and components of fodder additives